-2y=12-6

Simple and best practice solution for -2y=12-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2y=12-6 equation:


Simplifying
-2y = 12 + -6

Combine like terms: 12 + -6 = 6
-2y = 6

Solving
-2y = 6

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '-2'.
y = -3

Simplifying
y = -3

See similar equations:

| (5+2j)+(7+j)= | | -2y=12-12 | | ln(5x-3)+ln(x+2)=ln(5x^2+9) | | 3y=9-1 | | 9+13z=9-8z | | 1-4s=6s-7 | | 486=90x+4x^2 | | 7(6+4x)=210 | | 4.2x-3=-(3x+15) | | x+2x=6+3 | | (x-1)(4-x^2)=0 | | 6x-4x=12+4 | | (39-x)*(39-x)=(33-x)*(46-x) | | (39-x)*(39-x)=(33-x)*(39-x) | | -13x+2x=-39+24x | | 5t+9=11 | | 81-3x=11-10x | | 3(2a+1)=27 | | 3x+13=-50-6x | | 8+8x=1+x | | 1-45=6s-7 | | x^2+(2x)2=625 | | 4x^2+X^2+4x+2-70=0 | | 9y^2-12y+14=0 | | 6b-5=7-2b | | 9q+3w+7=15w+25+3q | | iz^2*3z+4i=0 | | 4x^2+x-70=0 | | 13u-3=4u+3 | | 5x+5=40-2x | | 20x-2=6x+5 | | +10p-10p=4-55+100 |

Equations solver categories